Strength and weakness of the totalitarianism in Wartime Soviet Union - Suprun, Mikhail (Septentrio Conference Series, 2015)
Unlike all other countries of the Barents Area, Russia found itself in a very specific situation. At the beginning of the war it entered into the alliance with the Axis, while from 1941 it continued the war in the Anti-Hitler coalition. But the main distinctive feature of the wartime Russia was the transformation of its policy. Not a single state in the world history had reached such a degree of centralization as the Soviet Union did during the Second World War. Along with an extremely high degree of centralization of the political system, the Soviet state completely subdued the economy in order to solve the main problem of the moment – to mobilize maximum resources in the shortest period of time in order to win the war. During the war it could be done only at the expense of the population’s welfare. As a result, during only the first months of the war the Soviet Union managed to compensate its huge losses in manpower, weapons and technology. At the same time, providing the population with food and manufactured goods had been reduced to the absolute minimum. Sometimes – less than the minimum. In some cities, e.g. Arkhangelsk, famine broke out. Soon it was followed by outbreaks of epidemics and high mortality. In order to avoid epidemics which threatened to develop into a pandemic that could spread into the army, the authorities were forced to take drastic measures to improve the healthcare system by including almost the entire population of the country in sanitary training. Control of the epidemic situation became another domestic front for Russia. Largely thanks to the strict centralization, the government managed to mobilize the population for victory at this "home front". At least in the Northern areas they managed to extinguish outbreaks of epidemic diseases, while several diseases were minimized or even eliminated by the end of the war. It is this particular nature of the Soviet totalitarianism and its manifestation in the North that is the research topic in Suprun’s article.